EVALI in teenagers: consequent modifications about the use of electronic cigarettes in this age gap (Research, Society and Development, 2022)
Electronic cigarettes, also known as Vape, Juul, and other names, arrived in Brazil as an attractive option for teenagers. At the beginning, the main goal was to use it as na alternative to conventional cigarettes., but it became another way into use of cigarettes and other drugs. The objective is to clarify the symptoms resultant of electronic cigarettes in teenagers, from 12 to 19 years, fitting the criteria to EVALI. This is a literature review, realized during April-July of 2022 through the keywords in the scientific online database: Scielo, MEDLINE (trough PubMed), Biblioteca Virtual em Saúde (BVS). As inclusive criteria, only articles between 2019 and 2022 were used, with describers above, without territorial restriction. In total, 31 articles were used in this review. The clinic presentation described by the authors may vary from respiratory symptoms as cough, dyspnea, fever, gastrointestinal symptoms as diarrhea, abdominal pain, and vomit, even convulsions probably associated with use of this electronic devices. Although the selling is prohibited in Brazil since 2009, the e-cig grew in popularity between teenagers. More Brazilian studies are necessary to identify early the other possible effects of this type of cigarettes. It’s also necessary that target population have access to information about the consequences of “vaping”.